Pharmacologic cardioversion with intravenous amiodarone is likely safe in neurocritically Ill patients. (May 2017) - Su, Michael; Seki, David; Moheet, Asma M.
Highlights: We evaluated the safety of cardioversion of new onset neurogenic atrial fibrillation in the brain injured patient using intravenous amiodarone. We found that pharmacologic cardioversion with intravenous amiodarone without anticoagulation is likely safe in the brain injured patient. Intravenous amiodarone may be considered for the treatment of atrial fibrillation in the brain injured patient. Abstract: Neurological injury is often associated with cardiac abnormalities, including electrophysiological issues. Cardioversion of acute atrial fibrillation (<48 h' duration) without anticoagulation carries about a 0.7% risk of thromboembolism. There is limited data on managing acute atrial fibrillation specifically in the neuroscience intensive care unit (NSICU) setting. We sought to determine the safety of using intravenous (IV) amiodarone for restoring sinus rhythm in patients with presumed new onset atrial or ventricular tachycardia after neurological injury. We conducted a retrospective review of consecutive patients admitted to our NSICU between June 2011 and March 2015 with a primary neurological diagnosis and new onset tachyarrhythmias who received IV amiodarone. Baseline demographics and presence of known risk factors for atrial fibrillation were recorded. The primary end point was new onset stroke. 48 patients were included for the final analysis. No patients developed new stroke after receiving IV amiodarone. The average follow up period was 14.0 days. The majority of patients did not have the pre identified risk factors for atrial fibrillation. Ischemic stroke and traumatic brain injury were the most common admitting diagnoses. We conclude that in patients with primary neurological injury, use of IV amiodarone for rhythm control of acute onset atrial fibrillation carries a low risk of cardioembolic stroke in the first 2 weeks. Further investigation, including prospective studies, with larger samples and longer follow up periods is warranted.